2021
DOI: 10.1017/s0014479721000168
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-time corrective dose fertilizer nitrogen management in wheat using atLeaf meter and leaf colour chart

Abstract: Fertilizer nitrogen (N) management in any region following standard general recommendations discount the fact that crop response to N varies between sites and seasons. To devise field-specific N management in wheat at jointing stage (Feekes 6 growth stage) using atLeaf meter and leaf colour chart (LCC), eight field experiments were conducted in three wheat seasons during 2017–2020 in the West Delta of Egypt. In the first two seasons, four experiments consisted of treatments with a range of fertilizer N applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The fact that N uptake in wheat is relatively slow at early growth stages and accelerates to a maximum around Feekes 6 growth stage supports the findings of this study (Doerge et al, 1991;Shukla et al, 2004;Tian et al, 2018;Ali et al, 2020). Several studies have found that using moderate doses of fertilizer N at planting and Feekes 2, followed by an adjustable dose at Feekes 6, worked better than the general recommendation (Bijay-Singh et al, 2002;Varinderpal-Singh et al 2012;Ali et al, 2021). The findings of this study are also supported by the work of Bijay-Singh et al (2011 and Ali (2020), who found that applying an NDVI-guided dose of N at the Feekes 5-6 stage of wheat produced yields equivalent to the general recommendation while using less total fertilizer N. An N management program that employs this concept will allow growers to determine the likelihood of an N response at harvest, thereby increasing their profit.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The fact that N uptake in wheat is relatively slow at early growth stages and accelerates to a maximum around Feekes 6 growth stage supports the findings of this study (Doerge et al, 1991;Shukla et al, 2004;Tian et al, 2018;Ali et al, 2020). Several studies have found that using moderate doses of fertilizer N at planting and Feekes 2, followed by an adjustable dose at Feekes 6, worked better than the general recommendation (Bijay-Singh et al, 2002;Varinderpal-Singh et al 2012;Ali et al, 2021). The findings of this study are also supported by the work of Bijay-Singh et al (2011 and Ali (2020), who found that applying an NDVI-guided dose of N at the Feekes 5-6 stage of wheat produced yields equivalent to the general recommendation while using less total fertilizer N. An N management program that employs this concept will allow growers to determine the likelihood of an N response at harvest, thereby increasing their profit.…”
Section: Discussionsupporting
confidence: 81%
“…It has been documented that applying fertilizer N more than the need of the crop results in substantial N losses and, as a consequence, low N use efficiency (Fageria & Baligar, 2005;Ladha et al, 2005;Bijay-Singh, 2018;Ali, 2020;Ali et al, 2021). The findings of the present study highlight the necessity for field-specific management strategies to synchronize fertilizer N supply with N demand by the crop.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…At 70 DAS, the requirements were 66.7, 50.5, 27.9, 22.9, 22.2, 15.5, and -16.6 kg N ha −1 , respectively. In general, wheat response to application of N fertilizer after Feekes 6 growth stage (around 55 DAS) is low (Bijay-Singh et al 2011;Ali 2020;Ali et al 2021), although the hypothetical N fertilizer requirement used at 70 DAS was only for comparison.…”
Section: Estimation Of N Requirements Depending On the Nc Dilution Curvementioning
confidence: 99%